Normal anterior cruciate ligament laxity in the Malaysian population - Kamarul, Tunku; Razif, A.; Elina, R.; Azura, M.; Ky, C. (2007)
A study to determine average knee laxity in the Malaysian population and how it affects daily living was conducted at the University Malaya Medical Centre between January and April 2004. Fifty two male and 76 female subjects were recruited for this study, all of whom were healthy volunteers with no ambulatory problems. Side to side knee laxity testing was performed using a KT-1000 arthrometer. Significant differences in knee laxity were noted among different races and between sexes. For instance, overall, Chinese and female study participants had higher knee laxity: (left knee, 2.17 mm (SD=1.30) and right knee was 2.88 mm (SD= 1.51)). On average, the difference between knees was 0.70 Â± 1.26 mm (less than 1 mm) which is a smaller variation than reported in previous studies which suggested 3 mm. Despite finding knee laxity ranging from 0 to 8mm, no correlations were found between Lysholm, IKDC and Tegner knee outcome scores and the degree of knee laxity. No other predictors such as height, weight and age correlated with levels of knee laxity. We therefore conclude that knee laxity is a common occurrence in the normal population and is therefore not suitable as a sole predictor of knee function and should not be used as the only criteria for surgical intervention.